An Investigation into Methods for Electrospinning Poly(ether ether ketone). - Keller, Thomas. (Tufts Archival Research Center, 2018)
Electrospinning is a well-established method for forming polymers into micron and sub-micron size fibers. During electrospinning a polymer in a liquid state, either in solution or molten, is drawn into a fibrous shape using applied high voltage. This thesis sets out to show a new method for electrospinning Poly(ether ether ketone) (PEEK). PEEK has thermal, chemical, and mechanical properties that make it desirable for many applications in filtration and textiles. However, these desirable properties also make PEEK a difficult material to process. It is insoluble in most common solvents at room temperature, with the exception of Sulfuric Acid at greater than 95% concentration. Yet, PEEK undergoes a reaction known as sulfonation when dissolved in Sulfuric Acid. Sulfonation adversely affects PEEK’s thermal and chemical properties. Therefore, this thesis provides a method for electrospinning PEEK without sulfonation, by electrospinning the polymer in a molten state rather than in solution. By keeping PEEK in its native, unsulfonated state, the resulting fibers are shown to retain their thermal and chemical properties. Furthermore, the fibers are shown to be of micron and sub-micron size. To the best of my knowledge, this thesis presents the first successful method for electrospinning native PEEK fibers.